Aristotle’s necessity and coincidences: An interpretation of Metaphysics VI 3 and XI 8 (2021)
This article presents an interpretation of two disputed passages from Metaphysics VI 3 and XI 8 i n w hich Aristotle’s reasoning is aimed at avoiding universal  necessity based on the existence of coincidences. This reasoning has given rise to multiple and incompatible interpretations from Antiquity to present day. In them, the Stagirite reasoning has been presented in a range that goes from understanding it as a position compatible with the strongest determinism, to one that requires a very general indeterminism. In dialog with these interpretations, a reading will be defended, according to which these  assages are designed to argue not against causal determinism but against predetermination.